Uncoupling proteins: are they involved in vitamin D3 protective effect against high-fat diet-induced cardiac apoptosis in rats?. (4th March 2022) - Alrefaie, Zienab; Awad, Hossam; Alsolami, Khadeejah; Hamed, Enas A.
Abstract: This study aimed to assess the impact of high-fat diet (HFD) and vitamin D3 supplementation on cardiac apoptosis, inflammation, oxidative stress, and cardiac uncoupling proteins (UCPs) 2&3 expression. Forty rats were fed either (45%) or (10%) fat diet with or without vitamin D3 (500 U/kg/day) for 6 months, then cardiac tissue expression of Bax, Bcl2, Fas, Fas-L (markers for apoptotic pathways), TNF- α, MDA7, GPX1 (inflammatory and oxidative markers) and UCP 2&3 were assessed. Results revealed the enhancement of intrinsic and extrinsic cardiomyocyte apoptosis cascades and increased inflammatory and oxidative burdens on the heart in HFD rats. Downregulation of UCP2 and upregulation of UCP3 gene expression at 6 months. After vitamin D3 supplementation with HFD, cardiac apoptotic, inflammatory and oxidative markers were mitigated and expression of UCP3 was downregulated and UCP2 was upregulated. This work highlights the novel cardioprotective effect of vitamin D3 in the experimental model of HFD feeding through the downregulation of UCP3.